Host Matrix Materials for Luminescent Solar Concentrators: Recent Achievements and Forthcoming Challenges - Griffini, Gianmarco (Frontiers in Materials, 2019)
Luminescent solar concentrators (LSCs) have attracted increasing attention in the past few years as appealing solar energy technology for the seamless integration of photovoltaic (PV) systems into the built environment. Traditionally, research in this field has focused on two main aspects: the optimization of the device assembly, in the quest for more efficient architectures to maximize collection, transport and conversion of photons into usable electrical energy; the development of novel, highly emissive luminescent species, to ensure broad light collection and efficient photon emission. Only recently, the attention has also been directed towards the selection and development of suitable host matrix/waveguide materials with appropriate optical properties, sufficient chemical compatibility with the guest luminescent species, good processability for easy device fabrication and prolonged durability in outdoor operation. In additional to consolidated polymeric systems based on polyacrylates or polycarbonates, in recent years different examples of alternative host matrix systems have been proposed, characterized by peculiar chemical, physical and optical characteristics specifically designed to meet the stringent requirements of the LSC technology. This mini-review will focus on recent developments in the design of new host matrix materials for LSC applications. An overview of the most recent examples of novel LSC host matrices will be provided here, mainly focusing on new polymers, polymer-based organic-inorganic hybrids and multifunctional organic systems. Finally, opportunities and challenges in the field will be considered in view of the effective exploitation of the LSC technology in real application scenarios.